Evaluation of the use of a clinical practice guideline for external apical root resorption among orthodontists - Sebastiaan P. van Doornik; Marlotte B. M. Pijnenburg; Krista I. Janssen; Yijin Ren; Anne Marie Kuijpers-Jagtman (SpringerOpen, 2024)
Abstract Background External apical root resorption (EARR) is a frequently observed adverse event in patients undergoing fixed appliance therapy. Assessing the patients' risk during treatment is important, as certain factors are assumed to be associated with an increased likelihood of occurrence. However, their predictive value remains limited, making evidence-based clinical decision-making challenging for orthodontists. To address this issue, the Dutch Association of Orthodontists (NvVO) developed a clinical practice guideline (CPG) for EARR in accordance with the AGREE II instrument (Appraisal of Guidelines for Research and Evaluation II) in 2018. The aim of this study is to get insight into the actual utilization and the practical implementation of the guideline among orthodontists. The hypothesis to be tested was that after its introduction, clinical practice for EARR has changed towards the recommendations in the CPG. Objective To investigate the use of the 2018 clinical practice guidelines for EARR among orthodontists 3 years after its introduction. Methods A questionnaire using a 7-point Likert scale was developed concerning four domains of EARR described in the guideline. The questionnaire was piloted, finalised, and then distributed digitally among Dutch orthodontists. REDCap was used for data collection, starting with an invitation email in June 2021, followed by two reminders. Effect was tested by the Mann-Whitney U test, and the influence of demographic variables was analysed. Results Questionnaires were sent out to all 275 and completed by 133 (response rate 48%); N = 59 females and N = 73 males were included; 81% had their training in the Netherlands, 89% had ≥ 6 years of work experience, and 89% worked in private orthodontic practice. One hundred thirty orthodontists (98.5%) reported changes in clinical practice. The biggest positive change in clinical behaviour regarding EARR occurred if EARR was diagnosed during treatment. Sex, clinical experience, country of specialist training, and working environment of the respondents did not affect clinical practices regarding EARR. Conclusions This questionnaire demonstrated that, 3 years after introduction of the guideline, orthodontists improved their self-reported clinical practices to a more standardised management of root resorption. None of the demographic predictors had a significant effect on the results.